The First Days of Jesus and the Role of the Disciples: A Study of John 1:19-51 - Moloney, Francis J. (Australian biblical review, 2017)
The Prologue to the Fourth Gospel (John 1:1-18) introduces the reader/listener to the narrative of 1:19-51. Set within the temporal markers of four days (1:29, 35, 43), leading into "on the third day" of 2:1, the narrative features the witness of the Baptist (1:19-34) and the vocation of the first disciples (1:35-51). The 'days' do not form a 'week' opening Jesus' ministry, but reflect a liturgical tradition surrounding the Jewish celebration of Pentecost. Unlike traditional biblical and especially Gospel vocation stories, the response of the disciples to Jesus matches neither the Christology of the Prologue nor the Christological witness of the Baptist. Their limited faith-response leads the reader/listener further into the narrative, asking questions about the nature of authentic Johannine faith.